Approaches to healing in Roman Egypt - Draycott, Jane Louise (2011)
This thesis examines the healing strategies utilised by the inhabitants of Egypt during the Roman period (from the late first century BC to the fourth century AD) in order to investigate how Egyptian, Greek and Roman customs and traditions interacted within the province. It explores the symbiotic relationship between 'professional' and 'amateur' medical practice within Egypt, and examines the ways in which three particularly well-attested health problems - eye complaints, febrile conditions and the injuries inflicted by wild animals - were approached, evaluated and treated. By considering a range of literary, papyrological, archaeological, and anthropological sources, this thesis argues that healing strategies were developed in response to a variety of historical, cultural and social factors, and were intimately connected to the region's climate, geography and natural resources. This thesis, then, presents a fresh and nuanced approach to understanding healing strategies in Roman provincial culture, identifies diagnostic features of healing in material culture and offers an integrated reading of ancient medical literary and documentary papyri, and archaeological evidence. By encompassing the full spectrum of healing strategies available to the inhabitants of the province, and by incorporating elements of medical, surgical, magical and religious healing, it offers a comprehensive and wide-ranging perspective on healing in Roman Egypt, and investigates new approaches to the study of medicine in the Roman world.